Pengaruh Dukungan Sosial Keluarga Dan Kecerdasan Emosi Terhadap Quater Life Crisis Pada Mahasiswa Pendidikan Administrasi Perkantoran Universitas Negeri Jakarta - Andaresta, Rika; Indrawati, Erdina (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This study aims to determine the influence of family social support and emotionalintelligence on final-year students at Universitas Negeri Jakarta. This researchemploys a quantitative method. The population of this study is 160, with a sample of 113respondents selected using simple random sampling. The data collection method utilized aLikert scale model. The data processing in this study was analyzed using Simple LinearRegression and Multiple Linear Regression methods through the JASP 0.18.3.0program for Windows. The results showed that: 1) there is an influence of family socialsupport on the quarter-life crisis (r = 0.767 and p < 0.05); 2) there is an influence ofemotional intelligence on the quarter-life crisis (r = 0.790 and p < 0.05); 3) there is aninfluence of both family social support and emotional intelligence on the quarter-life crisis(r = 0.001 and p < 0.05). This indicates that there is a significant influence of familysocial support and emotional intelligence on the quarter-life crisis of final-year studentsat Universitas Negeri Jakarta.